Tactics of Reporting Bad News in Professional Communication between a Doctor and a Patient - A. A. Markova; M. I. Barsukova (Архивъ внутренней медицины)
The article is devoted to the development of the level of communicative competence of future doctors and the peculiarities of professional communication with patients. The basis of the work were the questions of determining the speech behavior of a doctor in one of the most difficult communicative situations — the situation of delivering bad news. Based on the material of real recordings of doctors’ speech, the analysis of risky communicative steps in the communication between the doctor and the patient is carried out, the most effective ways of implementing the doctor’s speech tactics in the situation of bad news are determined. Conclusions are drawn about the need to improve the level of professional communication of doctors and to train medical students in the communication skills of delivering bad news.